El Buen Vivir como alternativa al desarrollo para América Latina - Cubillo-Guevara, A.P.; Hidalgo-Capitán, A.L.; García-Álvarez, S. (Revista Iberoamericana de Estudios de Desarrollo)
In this article we show the theoretical-regulatory basis of Good Living, understood as a transformation proposal of Latin American socioeconomic systems that aims to overcome the problems of bad development (alienation, inequality and unsustainability). So to achieve the objectives of identity, equity and sustainability, we propose a political strategy of the creation of a plurinational, post-capitalist and biocentric society.